Faktor - Faktor Penyebab Kudeta Terhadap Kekuasaan Moammar Khadafi di Libya - Jenni Irene Corry M; Karina Septiani; Maulana Diki (PERSPEKTIF, 2020)
In the concept of the internal conflict, Michael Brown explained there are political factors, economic, social, cultural and structural contribute to conflict within a country. The fourth order assist researchers in analyzing the causes of the coup against Moammar Gaddafi in Libya. During the 42-year reign of Moammar Gaddaf, the Libyan people have political issues such as curbs on political activity, political institutional discrimination, exclusive state ideology, significant internal political groups and the role of the political elite that interfere with the freedom of the people. Then economic issues such as economic discrimination, unemployment, and corruption in the Gaddafi’s family that give rise to high social inequalities. Coupled with the structural and socio-cultural factors such as discrimination against minorities, gender, and state institutions are not effective as inhibitors of the country's development. Gaddafi uses his own thoughts in undergoing government, by creating the Green Book rules as guidelines for political, economic, and social. Began when the Arab Spring swept Tunisian and Egyptian people who successfully staged a coup against their leader, there arises a sense of longing for the same freedom. Then triggered by the arrest of human rights campaigner who conducted the country's security forces in February 2011 and the blocking of internet sites in the emergence of large demonstrations - demanding the release of their scale and the overthrow of Moammar Gaddafi in the Libyan leadership.